Attachment of repeated sequences to the nuclear cage. - Jackson, D A (1984)
Nuclear DNA is probably organized into loops by attachment to a sub-structure in vivo. When HeLa cells are lysed in Triton and 2M NaCl the resulting nucleoids contain naked DNA which is supercoiled so the loops must remain intact. We have attempted to identify sequences responsible for attaching these loops to the nuclear sub-structure by progressively detaching DNA with various nucleases. Fragments at the 5' end of the ribosomal RNA locus, and a variety of transcribed and repeated sequences, are shown to lie relatively close to attachment points. This implies that sequences cannot be arranged randomly. However no "attachment sequence" could be identified.